VISUAL SYSTEM OF WAYANG KAMASAN PAINTING ART - Putra Adnya, Made Chandra; Budiaprilliana, Luh; Suryadinata T.Y., Anak Agung Gde Trisna (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2026)
Iconography plays a crucial role in the visual interpretation of Wayang Kamasan, wherein various symbols and icons are embedded within a complex system that warrants in-depth analysis. This study, therefore, centers on the archiving and examination of iconography within the Wayang Kamasan painting tradition. The author conducts a stylistic documentation of several painters who are heirs to this tradition to map contemporary artistic tendencies in Kamasan. The rationale for this research arises from the paucity of scholarly inquiry into the visual aspects and creative processes, particularly the transformation of textual narratives into visual imagery. Under the auspices of the Gurat Institute, this research deconstructs the visual elements and narrative structures inherent in Kamasan painting. The objective is to systematically document and deepen the understanding of the formal structures and narrative strategies employed by the artists, while simultaneously fostering opportunities for novel explorations in iconography and thematic development.